Modeling The Marketing Technology Adoption Decision (Martech): Factors of Influence - Mihai-Cristian ORZAN; Raluca-Giorgiana (POPA) CHIVU; David-Florin CIOCODEICĂ; Ionuț-Claudiu POPA; Ana Maria RANCEA; Ana-Maria DUMITRACHE (BĂJAN) (Communications of International Proceedings, 2022)
The concept of "Martech" refers to technology (of any type, namely tools, software, platforms and applications) used for the purpose of making the marketing activity more efficient. Martech is used to easily create and manage large volumes of data, to measure the performance of promotional campaigns, to monitor and facilitate online research and analysis, and to improve consumer experiences. However, like every evolutionary technological element, for the adoption and implementation of new marketing technologies, a series of updates are necessary at the level of each company, whether it is human adaptation (learning and acquiring new knowledge and skills for using marketing technologies ) or technical adaptation (acquisition of new software and hardware solutions that allow the running in appropriate conditions ofmartech technologies). This fact obviously leads to reluctance and non-acceptance for reasons such as the limitation of human or financial resources. In this article, we wanted to highlight the factors that contribute to the adoption of marketing technologies. Thus, a quantitative research was carried out among a sample of managers or employees in the marketing departments of the companies, and based on their results, a conceptual model was built (using SEM analysis) that indicates the links and their intensity between the contributing factors to the adoption of marketing technologies.
Keywords: martech; marketing technology; factor of influence.